To assess the accuracy of Plusoptix S12-C photoscreener in detecting amblyogenic risk factors in children aged 6 months to 6 years in remote areas of South India - Kaur, Kirandeep (Indian J Ophthalmol, 2020)
PURPOSE: To assess the screening accuracy of a novel fourth generation, handheld Plusoptix S12 C photo screener in detecting amblyogenic risk factors in children aged 6 months to 6 years in remote areas of South India. METHODS: In this cross sectional study, 381 children aged 6 months to 6 years were screened by a trained fieldworker in Anganwadis and schools using the Plusoptix photoscreener. This was followed by complete ophthalmic evaluation including retinoscopy, subjective refraction, and strabismus evaluation by an optometrist and an orthoptist. All children further underwent complete ocular examination by the senior pediatric ophthalmologist for validation of the results. RESULTS: A total of 367 children were included in the study. The sensitivity and specificity of the photo screener were found to be 86.76% and 82.27%, respectively. Positive Predictive Value, Negative Predictive Value, and Receiver Operative Characteristics were 52.67%, 96.47%, and 83.11%, respectively. In subgroup younger than 3 years, sensitivity and specificity was 89.19% and 81.18%, respectively. Myopic astigmatism was the most common amblyogenic risk factor in our study group. CONCLUSION: In India, with a lack of adequate healthcare professionals and poor health-seeking behavior; photo screeners can play an important role. We recommend the use of photo screeners for screening children as young as 6 months, especially in remote low-resource settings. This will help in expanding reliable eye care services to previously underserved areas.